2016
DOI: 10.1038/npjpcrm.2016.82
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities to develop the professional role of community pharmacists in the care of patients with asthma: a cross-sectional study

Abstract: There are many indications in Australia and globally that asthma management is suboptimal. Ideally, patients need to proactively self-manage the condition with the support of health professionals. Community pharmacists are a highly accessible resource for patients but currently provide inconsistent services. General practitioners also face many barriers to the provision of chronic disease management for asthma patients. The aim of this research was to characterise patients with asthma who present to community … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(45 citation statements)
references
References 48 publications
1
43
0
1
Order By: Relevance
“…A previous study showed a discordance in patients' perception of asthma control and their actual asthma control comparing their personal impressions and perceptions with the results of another questionnaire to measure asthma control, the “Asthma Control Test”, with a high percentage of patients feeling controlled despite their test results showing an uncontrolled asthma. 23 Implying this into interpretation of our study's results gives additional support to consider symptom scores and lung function separately.…”
Section: Discussionsupporting
confidence: 56%
“…A previous study showed a discordance in patients' perception of asthma control and their actual asthma control comparing their personal impressions and perceptions with the results of another questionnaire to measure asthma control, the “Asthma Control Test”, with a high percentage of patients feeling controlled despite their test results showing an uncontrolled asthma. 23 Implying this into interpretation of our study's results gives additional support to consider symptom scores and lung function separately.…”
Section: Discussionsupporting
confidence: 56%
“…This study extends the knowledge in pharmacy literature by exploring patients’ experiences of asthma within the movement toward patient-centred care in pharmacy practice. Previous studies that examined pharmacists’ contribution to asthma care found that pharmacists possess the skills and competencies required to support patients with self-management education, demonstrating inhaler technique, and monitoring asthma therapy and could do more for patients in therapy monitoring and follow-up [7,8,38]. Findings from prior studies highlight the need for community pharmacists to work together with patients to attain control of their asthma.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for poor asthma management are multifaceted including the disease itself, presence of comorbidities, patients’ self-management, healthcare professionals’ care, or the interaction among these factors [5,6]. Medication therapy is the primary intervention used in asthma highlighting asthma patients have needs that pharmacists can address [7,8]. Pharmacists frequently encounter asthma patients and are not only well placed to identify patients with poorly controlled asthma but also resolve medication problems, educate patients on inhaler technique, monitor therapy, and develop personalised asthma action plans [8,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Prescribing by pharmacists has been reported in the management of chronic diseases requiring frequent monitoring and dose adjustments, including conditions requiring anticoagulation therapy, hypertension, diabetes mellitus, asthma and dyslipidaemia. Pharmacist prescribing and management interventions in these conditions improved blood pressure, glycaemic, INR and lipid level control, quality of therapy, adherence and cost‐effectiveness …”
Section: Introductionmentioning
confidence: 99%
“…Pharmacist prescribing and management interventions in these conditions improved blood pressure, glycaemic, INR and lipid level control, quality of therapy, adherence and cost-effectiveness. [11][12][13][14][15][16][17][18][19][20][21][22] This study proposes a framework for pharmacist prescribing for chronic conditions in a hospital setting within a multidisciplinary approach. The proposed framework includes specific clinical guidelines developed for three therapeutic scenarios considered in this study, namely conditions requiring oral anticoagulation therapy, hypertension and diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%